THE EFFECT OF MINIMUM WAGE INCREASING TO UNEMPLOYMENT RATE IN INDONESIA FOR PERIOD 1992–2010 - Yuventus Effendi (Pusbindiklat - LIPI, 2012)
This research is trying to explain Indonesian empirical evidence about minimum wage increasing effecttowards unemployment. Minimum wage increasing should become a benefit for labour force. Unfortunately, macroeconomicstheory stated that the effect of minimum wage increasing has positif correlation with labour surplus.Research method that will be used in this paper is simple regression by using panel data. The result of this researchis increasing minimum wage will be significantly affect unemployment for period 1992–2010, in Indonesia. Forevery 10% minimum wage increasing will affect unemployment about 11,35% positively. This research also findthat for every province there will be a different unemployment increasing percentage possibly depends on cost ofproduction, labour surplus, and provincial GDP.